O ENSINO JURÍDICO NA UNIVERSIDADE FEDERAL DO MARANHÃO CAMPUS II (IMPERATRIZ): RESGATE DA SUA HISTÓRIA E IMPORTÂNCIA PARA A REGIÃO TOCANTINA - Medrado, Elizon de Sousa (2007)
The present work has for central objective the ransom of the history of the juridical teaching of the Federal University of Maranhão, especially the Campus II (Imperatriz), making an analysis for to discuss, among other subjects, the reasons that determined the coming of the juridical teaching the Imperatriz, your creation and implantation in Imperatriz, the first vestibular exam and the beginning of the course of Right; the difficulties faced in the beginning of your implantation. It s still seeks to investigate the contribution and Campus II'S importance for the Area Tocantina, besides establishing critics to your performance and the absence of a Pedagogic Project. The work still makes an approach about the education in Brazil in your principal periods, preceding to the analysis of the juridical teaching in Brazil, in that it will be discoursed on your origin, evolution and the transformations and reforms, as well as on the problems and the crisis that he has been facing along the years, besides to show the elements that propitiate rediscovered of your role in the society. Related to the methodology, it was adopted the qualitative approach, in order to give the possibility of understanding the topic, once this research was not limited by the choose of data collect instruments, but moreover it went throughout the analysis and interpretation of the information into the process of investigation, which allowed toreceive the mandatory critics from the material that was collected in this research. Through this way, the data collect was developed by bibliographic research, documental analysis and demi-structurated interviews. Finally, the work presents the results of the research and it concludes demonstrating that, in spite of the difficulties faced in all your path, the Campus II (Imperatriz) has been giving great contribution for the Area Tocantina, what denotes your importance, once it democratized the juridical teaching in that area.